Review Artikel: Evaluasi Penerapan Disiplin Protokol Kesehatan Sebagai Upaya Pemulihan Pariwisata Di Bali - Luh Gede Nita Sri Wahyuningsih; I Made Rai Mahardika; Ayu Lestari (Jurnal Kesehatan Medika Udayana, 2022)
Background: The discipline of health protocols is one of the first steps for the revival of tourism in Bali, which during the pandemic period experienced very difficult phases for tourism activists as well as local, domestic and international tourists. Bali Rise is Bali's tag line to re-open itself to accept tourists from abroad, of course with a health protocol that has become an absolute price. Purpose: The purpose of this article review is to evaluate the application of health protocol discipline, especially in Bali. Method: the method used in this article review is to search for articles with the keywords health and tourism protocols. The inclusion criteria are literature on health protocols during a pandemic with a range of publication years from 2019 to 2021, while the exclusion criteria are review articles. The results of the literature search carried out deletion of double articles, screening of titles, abstracts, and full-text obtained 20 articles. Result: tourism activists in Bali have increased their attention to support the recovery of Bali tourism by participating in training and socialization of health protocols and even some tourist objects that make strict SOPs regarding the implementation of health protocols. Conclusion: tourism in Bali is ready to rise with the application of health protocol discipline